Triassic Sedimentary Filling and Closure of the Eastern Paleo‐Tethys Ocean: New Insights From Detrital Zircon Geochronology of Songpan‐Ganzi, Yidun, and West Qinling Flysch in Eastern Tibet. Issue 2 (27th February 2019) - Jian, Xing; Weislogel, Amy; Pullen, Alex
Abstract: Triassic flysch in the Songpan‐Ganzi Complex (SGC), eastern Tibet, is an important and rich record of tectonism associated with evolution and closure of the eastern Paleo‐Tethys Ocean. However, current models for tectonic evolution of the ocean remain controversial, in large part due to ambiguity of the origin of SGC deposits. We constrain provenance of Middle‐Upper Triassic turbidites from central SGC and the adjacent Yidun and West Qinling terranes by using detrital zircon U‐Pb geochronology. The results show that the detrital zircon ages mainly comprise five populations: 240–310 Ma; 400–480 Ma; 750–1, 000 Ma; 1, 700–2, 000 Ma; and 2, 300–2, 600 Ma. These ages indicate the East Kunlun and North China block served as major sediment sources for most of central SGC and West Qinling. The predominance of Paleozoic zircons in Upper Triassic turbidites indicates uplift and exhumation of the East Kunlun orogen during the Late Triassic. The southern SGC and Yidun turbidites display quite similar zircon age spectra (significant age peaks at approximately 1, 850 Ma), implying that Songpan‐Ganzi and Yidun depocenters were adjacent to each other by the Middle Triassic. This finding suggests that the Ganzi‐Litang Ocean, as a part of eastern Paleo‐Tethys Ocean, probably had been closed by the Middle Triassic. We favor subsequent deformation and uplift of the Triassic flysch was coeval with or possibly predated latest Triassic shortening within the Longmenshan thrust belt, resulting in recycling of the flysch into surrounding sedimentary basins (e.g., Sichuan and Qamdo basins) since latest Triassic time. Key Points: Amalgamation of the Songpan‐Ganzi Complex and Yidun terrane, and closure of the Ganzi‐Litang Ocean, had occurred by the Middle Triassic The East Kunlun, on northern margin of the eastern Paleo‐Tethys, underwent significant exhumation and erosion during the Late Triassic Deformation of the Songpan‐Ganzi and Yidun flysch strata was coeval with or predated latest Triassic shortening within Longmenshan